Pengaruh Pijat Oksitosin Terhadap Produksi ASI Ibu Menyusui di Wilayah Kerja Puskesmas Sidomulyo Rawat Jalan Pekanbaru - Magdalena Magdalena; Dina Auliya; Usraleli Usraleli; Melly Melly; Idayanti Idayanti (Universitas Batanghari Jambi, 2020)
Breast milk (ASI) is the best food for babies, because breast milk contains all the nutrients needed in the right amount and balance and contains immunity or antibodies that function to protect babies from various germs and diseases. one of the main obstacles of a mother in breastfeeding is because the milk production is not smooth. The method that can be done to facilitate ASI production is to do oxytocin massage on breast milk production in breastfeeding mothers in the Sidomulyo Outpatient Health Center Working area conducted on March 21-19 2019. The sample was taken as many as 16 respondents where respondents were observed before and after the intervention using sheets observation. This research is quantitative with a pre-experimental design and one group pretest posttest approach. Data were analyzed using Wilcoxon statistical test and it was found that the Z frequency of breastfeeding frequency was -3,573a and p-value was 0,000 while the Z value of frequency of infant urination was -3,547a and p-value was 0,000, which means (p <0,05 ) These results indicate the influence of oxytocin massage on nursing mothers. Thus, this study is expected to be recommended to health workers to provide knowledge on how to increase breast milk production in nursing mothers through oxytocin massage.